Anthocyanin-Rich New Zealand Blackcurrant Extract Supports the Maintenance of Forearm Blood-Flow During Prolonged Sedentary Sitting - Barnes, Matthew J.; Perry, Blake G.; Hurst, Roger D.; Lomiwes, Dominic (Frontiers in Nutrition, 2020)
Objectives: We examined the acute effects of anthocyanin-rich New Zealand blackcurrant extract and a placebo on hemodynamics during 120 minutes of sedentary sitting in healthy males. Additionally, we investigated whether changes in resting hemodynamics altered repeated isometric hand-grip exercise performance and post exercise forearm blood flow (FBF). Methods: Ten healthy males completed two trials during which they ingested either blackcurrant extract (1.87 mg total anthocyanins/kg bodyweight) or placebo powder. Heart rate, blood pressure and forearm blood flow were measured, and venous blood was sampled, prior to and 30, 60, 90 and 120 min-post ingestion. Participants remained seated for the duration of each trial. At 120 min post-ingestion participants completed as many repetitions of isometric hand-grip contractions as possible. Results: Heart rate, blood pressure and mean arterial pressure changed over time (all p < 0.001) but did not differ between treatments. A treatment x time interaction for FBF (p = 0.025) and forearm vascular resistance (FVR) (p = 0.002) was found. No difference in the number of isometric hand-grip contractions was observed between treatments (p = 0.68) nor was there any treatment x time interaction in post-exercise FBF (p = 0.997). Plasma endothelin-1 (p = 0.023) and nitrate (p = 0.047) changed over time but did not differ between treatments (both p > 0.1). Plasma nitrite did not change over time (p = 0.732) or differ between treatments (p = 0.373). Conclusion: This study demonstrated that acute ingestion of a single dose of blackcurrant extract maintained FBF and FVR during an extended period of sitting; however, this did not influence exercise performance during hand-grip exercise.